The genus Ancylosis Zeller, 1839 (Lepidoptera: Pyralidae: Phycitinae) from Ningxia Shapotou Nature Reserves of China - Gulzar, Abdukirim; You, Wanxue; Ren, Yingdang; Li, Houhun (Zootaxa, 2025)
Seventeen species of the genus Ancylosis are recognized from Ningxia Shapotou Nature Reserves of China. Three species are described as new: A. byuni Gulzar & Li, sp. nov., A. lativalvata Ren & Li, sp. nov. and A. ningxiana Li & Ren, sp. nov. Five species, A. roscidella (Eversmann, 1844), A. gozmanyella (Roesler, 1970), A. reginella (Roesler, 1970), A. plumbatella (Ragonot, 1888) and A. bulganella (Roesler, 1970), are newly recorded for the Chinese fauna. The males of A. plumbatella and A. bulganella are described for the first time. Images of adults and genitalia of the new species are provided.